Optical Properties of Sn Doped ZnO Thin Film Prepared Using Sol-Gel Method for Optical Limiting Application - Mudfer Alqaisi, Marwa; J. Ghazai, Alla (Al-Nahrain Journal of Science, 2021)
In this work, pure Zinc oxide and tin doped Zinc oxide thin films nanoparticles with various volume concentrations of 2, 4, 6, and 8 V/V% were prepared by using the sol-gel method. The optical properties were investigated by using UV-Visible spectroscope, and the value exhibits the direct allowed transition. The average of transmittance was around (17-23) % in visible region. The optical energy band gap was calculated with wavelength (300-900) nm for pure ZnO and Sn doped ZnO thin films which decreases with increasing concentration from 3.4 eV to 3.1 eV respectively and red shift. The real dielectric (εr) and the imaginary dielectric εi are the same behavior of the refractive index(n) the extinction coefficient (k) respectively. The optical limiting properties were studied by using an SDL laser with a wavelength of 235 nm. Pure ZnO and doping thin films an found efficient as optic limiting and depend on the concentration of the all samples.